The issue of stress in neoplastic disease - Lelonek, Barbara; Cieślik, Aleksandra; Kamusińska, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2013)
According to Selye stress is a body’s response to stimuli. Modern psychology defines stress as an adaptive and dynamic relationship between the abilities of individuals and the requirements of the situation (stress factors); characterized by a lack of balance. Stressors are ubiquitous and unavoidable, but do not cause clearly negative effects on individuals. The results of people activities depend on the available resources useful to cope with stress. Neoplastic disease exemplifies a special type of stressful situation; it acts as the biological stressor which affects the activity of the body, and the mental stressor which has an indirect effect on mental health and functioning of human being. It affects the body in a multilateral way, entails serious cognitive, emotional and behavioural consequences. Stress caused by neoplastic disease has its origin in somatic ailments, threat to life, prognostic indicators, troublesome therapeutic process and change in personal and professional situation. Emotional reactions to neoplastic disease are changing thanks to new information, worsening symptoms, methods of treatment; and they proceed in stages. From among above mentioned reactions the specialists can distinguish: the correct response which is in the final adaptation to neoplastic disease, and pathological response which emphasizes the inadequacy of one’s recognized disease. Nursing Topics 2013; 21 (1): 128–136